2021
DOI: 10.1007/s00134-021-06558-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adjunctive vitamin C, glucocorticoids, and vitamin B1 on longer-term mortality in adults with sepsis or septic shock: a systematic review and a component network meta-analysis

Abstract: We aimed to compare the effects of vitamin C, glucocorticoids, vitamin B1, combinations of these drugs, and placebo or usual care on longer-term mortality in adults with sepsis or septic shock. MEDLINE, Embase, CENTRAL, ClinicalTrials.gov and WHO-ICTRP were searched. The final search was carried out on September 3rd, 2021. Multiple reviewers independently selected randomized controlled trials (RCTs) comparing very-high-dose vitamin C (≥ 12 g/day), high-dose vitamin C (< 12, ≥ 6 g/day), vitamin C (< 6 g/day), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
2
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 54 publications
2
62
2
3
Order By: Relevance
“…However, the present results should be interpreted with caution because the difference of mortality was extremely small. The finding that vitamin C of ≥ 5 days was associated with an even greater decrease in mortality is consistent with previous meta-analysis suggesting that there may be a dose–response relationship between vitamin C and mortality [ 13 ]. Additional randomized trials evaluating very high-dose, long-term vitamin C for sepsis are warranted.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, the present results should be interpreted with caution because the difference of mortality was extremely small. The finding that vitamin C of ≥ 5 days was associated with an even greater decrease in mortality is consistent with previous meta-analysis suggesting that there may be a dose–response relationship between vitamin C and mortality [ 13 ]. Additional randomized trials evaluating very high-dose, long-term vitamin C for sepsis are warranted.…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, the CITRIS-ALI trial tested a higher dose of vitamin C (200 mg/kg/day) and found a significant decrease in mortality among patients with sepsis and acute respiratory distress syndrome [ 7 ]. Interestingly, a recent meta-analysis revealed the associations between high-dose (≥ 6 to < 12 g/day) and very high-dose (≥ 12 g/day) vitamin C and decreased mortality [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations